Effects of Purified Anthocyanins in People at Risk for Dementia: Study Protocol for a Phase II Randomized Controlled Trial - Khalifa, Khadija; Bergland, Anne Katrine; Soennesyn, Hogne; Oppedal, Ketil; Oesterhus, Ragnhild; Dalen, Ingvild; Larsen, Alf Inge; Fladby, Tormod; Brooker, Helen; Wesnes, Keith A.; Ballard, Clive; Aarsland, Dag (Frontiers in Neurology, 2020)
Background: The number of people with dementia is increasing, with huge challenges for the society and health-care systems. There are no disease-modifying therapies available. There is therefore an urgent need to identify strategies to reduce the risk for developing dementia. Anthocyanins are a class of compounds found in dark berries and fruits with a number of effects that might reduce the risk for cognitive decline and the development of dementia in elderly people. Aim: This Phase II three-centre, randomised, 24-week, placebo-controlled study, ongoing in Norway, aims to evaluate the safety and efficacy of anthocyanins in modifying key dementia-related mechanisms and maintain cognitive functioning in older people at risk for dementia. Methods: Participants (220 individuals aged 60-80 years) who meet the inclusion criteria (either mild cognitive impairment (MCI) or two or more cardiometabolic disorders (CMD)) are being enrolled in this study at three different centres in Norway. Participants are block randomised to identically appearing capsules containing 80 mg of natural purified anthocyanins or placebo 1:1. Dosage is 2+2 capsules per day for 24 weeks. The primary outcome will be the Quality of episodic memory score, a composite measure from the extensively validated online cognitive test battery CogTrack® which is administered at baseline, and monthly for the next 6 months. Secondary outcomes include other major scores from CogTrack; as well as a range of neuroimaging and other biomarkers. Anthocyanin metabolites will be measured in blood and cerebrospinal fluid. The change from baseline scores will be subject to Mixed Model for Repeated Measures (MMRM) ANCOVA. The primary comparison will be the contrast (difference in least square means) between active and placebo at the end of study (week 24). The primary study population will be a modified intention-to-treat population (clinicaltrials.gov, NCT03419039.). Discussion: This study aims to demonstrate whether there are beneficial effects of purified anthocyanins on cognition and on relevant biological functions in people at increased risk for dementia. Forthcoming results may contribute to further improvement of intervention strategies to prevent or delay the onset of dementia, including a potential decision to take anthocyanins towards Phase III trials.